High isolation of SPDT PIN diode switch using switchable dumbbell-shaped DGS in millimeter wave 28 GHz band - Mohd Yasin, Fatin Nadiah; Shairi, Noor Azwan; Othman, Adib; A. Majid, Huda; Zakaria, Zahriladha; Mohd Ibrahim, Imran; Jamaluddin, Mohd Haizal (Bulletin of Electrical Engineering and Informatics, 2023)
This paper proposes a high isolation of single pole double throw (SPDT) PIN diode switch using switchable dumbbell-shaped defected ground structure (DGS). The proposed SPDT switch was designed for radio frequency (RF) front-end transceiver of antenna array multiple input multiple output (MIMO) in millimeter wave 28 GHz band. The switchable dumbbell-shaped DGS can be switched between allpass and bandstop responses where the bandstop response of the DGS can be utilized as a high isolation in the SPDT PIN diode switch circuit. A simple mathematical analysis is explained in this paper for the bandstop and allpass responses of the switchable dumbbell-shaped DGS. The propose SPDT switch was designed based on Roger RT/Duroid 5880 with 0.254 mm thickness and relative dielectric constant of 2.2. The simulated result showed that the proposed SPDT PIN diode switch produced an isolation of 36.36 dB at 27.3 GHz (center of 28 GHz band), which was 63% higher than the conventional SPDT design.